Visible light mediated Iron-Catalyzed synthesis of C-3 alkylated Indoles, bisindolylmethanes and flavanones using alcohols. (12th April 2023) - Waheed, Mohd; Alsharif, Meshari A; Issa Alahmdi, Mohammed; Mukhtar, Sayeed; Parveen, Humaira
Graphical abstract: Abstract: An environmentally benign, mild approach for synthesis of C-3 alkylated indoles, bisindolylmethanes and flavanones using alcohols at room temperature under visible light has been developed. The reported reaction conditions were favorable for a wide range of alcohols afforded good to excellent yields of the respective products. Additionally, the reaction system was successfully extended to the synthesis of flavanones from 2-hydroxyacetophenone. The low cost and air stable Knölker iron catalyst has been employed for the dehydrogenation of alcohols under photolysis that would usually require a higher temperature.